2021
DOI: 10.3389/fcvm.2020.617561
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Clinical Features of Noncompaction Cardiomyopathy in the Fetal Population

Abstract: Objectives: Noncompaction Cardiomyopathy (NCCM) has been classified as primary genetic cardiomyopathy and has gained increasing clinical awareness; however, little is known about NCCM in the fetal population. We aimed to investigate the clinical characteristics and genetic spectrum of a fetal population with NCCM.Methods: We retrospectively reviewed all fetuses with a prenatal diagnosis of NCCM at a single center between October 2010 and December 2019. These cases were investigated for gestational age at diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
0
23
0
3
Order By: Relevance
“…For the quantitative analysis, 40 articles [121, were secondarily excluded. Of these, three papers focused on fetal demises or stillbirths [256][257][258], three papers focused on information postmortem [242,250,254], three were case reports [238,246,252], five focused on a single specific phenotype [240,241,248,261,274], three presented inhomogeneity in inclusion criteria and chromosomal anomalies/CNV assessment [239,251,262], six included both fetuses and postnatal cases [244,249,253,259,260,269], three focused on candidate genes [243,247,263], three focused on recurrent phenotypes or previously described cohorts [245,255,272], five were excluded for the lack of inclusion or eligibility criteria [264,265,268,271,276], two were excluded for the higher a priori risk for consanguinity and recurrence [266,270], one because parents were tested for recessive disorders [267], two because they focused on gene panels [273,275], and one due to the postnatal diagnosis [121].…”
Section: Exome Sequencingmentioning
confidence: 99%
“…For the quantitative analysis, 40 articles [121, were secondarily excluded. Of these, three papers focused on fetal demises or stillbirths [256][257][258], three papers focused on information postmortem [242,250,254], three were case reports [238,246,252], five focused on a single specific phenotype [240,241,248,261,274], three presented inhomogeneity in inclusion criteria and chromosomal anomalies/CNV assessment [239,251,262], six included both fetuses and postnatal cases [244,249,253,259,260,269], three focused on candidate genes [243,247,263], three focused on recurrent phenotypes or previously described cohorts [245,255,272], five were excluded for the lack of inclusion or eligibility criteria [264,265,268,271,276], two were excluded for the higher a priori risk for consanguinity and recurrence [266,270], one because parents were tested for recessive disorders [267], two because they focused on gene panels [273,275], and one due to the postnatal diagnosis [121].…”
Section: Exome Sequencingmentioning
confidence: 99%
“…The prevalence of CHD in LVNC was 20-50% depending on recruitment criteria, with VSD being the most common associated CHD (27-35%), followed by Ebstein's anomaly, atrial septal defect, and transposition of great arteries (1,2,6,18,22). When focusing on severe perinatal-onset LVNC, the higher prevalence of VSD (37-62%) was observed (21)(22)(23) and that apical muscular subtype appeared to be an unusually frequent finding compared with the general low prevalence, 10-20% (17).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of a large cohort of LVNC in fetal population showed a positive genetic test at 47% (9/20) and that mutations of non-sarcomeric genes accounted for the vast majority, including de novo dominant mutations of KCNH2 and PRKAG2 genes and maternally inherited X-linked gene mutations of NONO , with the exception of one case harboring a de novo mutation of a sarcomeric gene, TPM1 ( 21 ). The authors proposed that LVNC in fetal population with intrauterine onset heart failure might represent a unique entity and had distinct genetic spectrum ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…WES was performed as previously described [ 7 9 ]. Briefly, gDNA was extracted, hybridized, and enriched for sequencing.…”
Section: Methodsmentioning
confidence: 99%